Towards an anti-racist Physical Education: the protagonism of CEAFRO from Vitoria and Cariacica in Espírito Santo (Práxis Educativa, 2022)
This study analyzes the ethnic-racial educational programs of the last ten years in the municipalities of Vitória and Cariacica, in the state of Espírito Santo, Brazil. Specifically, it analyzes the actions and their effectiveness, and it seeks to identify the intervention of Physical Education within the context of these programs. The methodology followed two paths: a) studies of institutional documents with ethnic-racial proposals; b) semi-structured interview with agents from the Comissão de Estudos Afro-Brasileiros – CEAFRO (departments of African-Brazilian studies) of the Secretariats of Education of the municipalities mentioned above. The study revealed that the elements of corporeal culture are not instruments that are conducive to overcoming racial conflicts existing in the school context; there are close relations between CEAFRO and the organized institutions of society; and the teachers who adhere to such programs are activists and/or participants in ethnic-racial causes.Keywords: Physical Education. Ethnic-racial. Educational programs.